2018
DOI: 10.1111/1745-5871.12322
|View full text |Cite
|
Sign up to set email alerts
|

Inherited memory, social learning, and resilience: lessons from Spain's Great Blizzard of 1888

Abstract: The snowstorms that affected the Cantabrian Mountains in the winter of 1888 caused unprecedented damage, and the absence of a “resilient approach” to this episode had several consequences worth further consideration. In this study, we explored interconnections between and among memory, social learning, and resilience by surveying the affected landscapes, conducting interviews with current residents, and reviewing historical sources such as press archives. The mixed method has enabled us to examine the construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…More than 1,000 buildings collapsed, almost 20,000 livestock died, essential working tools were lost, harvests were ruined, and there was serious damage to farmland. Moreover, damage to infrastructure caused significant difficulties for supplies and exchanges for many months after the events (García‐Hernández et al, 2019). The situation thus had the potential to cause significant socioeconomic disruptions and health impacts in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 1,000 buildings collapsed, almost 20,000 livestock died, essential working tools were lost, harvests were ruined, and there was serious damage to farmland. Moreover, damage to infrastructure caused significant difficulties for supplies and exchanges for many months after the events (García‐Hernández et al, 2019). The situation thus had the potential to cause significant socioeconomic disruptions and health impacts in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Lin (2010) associated natural disasters with a decrease in fertility in Italy between 1820and 1962and in Japan between 1671and 1965 In the United States, Raker (2020) showed that severe tornadoes led to notable compositional changes in local population, and, in south-eastern Arabia, Petraglia et al (2020) found ancient droughts corresponded with the decline of inland occupations and population movements. In Spain, studies also considered long-term effects of historical disasters (for example, Alberola-Rom a, 2019; García-Hern andez et al, 2019;García-Torres, 2017;Gil-Guirado, 2017), but only Cuadrat et al (2016) delved specifically into their demographic impact, examining the effects of mid-seventeenth century droughts in the Central lands of the Ebro Valley, showing the event's correspondence with a sharp decline in the birth rate and a strong increase in mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ways in which both normal and extreme weather are understood, remembered, memorialised and recorded determines how descendants understand risk emergent from those extremes, and how climate and climate changeis positioned and contextualised (Hall and Endfield, 2016;Lorenzoni and Pidgeon, 2006;Palutikof et al, 2004). A growing literature is also demonstrating the importance of considering the complex long-term processes behind remembering and forgetting past disasters when developing disaster risk reduction (DRR) policies (García-Hernández et al, 2019;Garde-Hansen et al, 2017;McKinnon, 2019;McKinnon and Cook, 2020;Simpson and Corbridge, 2006). However more research is needed, and comparatively speaking, there are still few studies into the memory of extreme events or weather and how this influences vulnerability (Adamson, 2012;Endfield and Veale, 2017;Jones et al, 2012).…”
mentioning
confidence: 99%